Implantation of atelocollagen sheet for vocal fold scar - Kishimoto, Yo (2010)
PURPOSE OF REVIEW: This article reviews recent advances in scaffold-based interventions for the treatment of vocal fold scarring, with a particular emphasis on atelocollagen sheet implantation in the vocal fold lamina propria. RECENT FINDINGS: Scaffold-based therapies have demonstrated therapeutic promise in both pre-clinical and early clinical studies. Recent research has begun to shed light on the interactions between scaffold material properties, encapsulated and infiltrating cells, stimulatory molecules such as growth factors, and external regulatory variables such as stress, strain and vibration. The atelocollagen sheet, a cross-linked collagen material with abundant micropores, has an established clinical track record as a scaffold for dermal and epidermal repair and exhibited potential therapeutic benefit in a recent study of patients with vocal fold scarring and sulcus vocalis. SUMMARY: Scaffolding is one of the useful tools in tissue engineering and atelocollagen sheet implantation has shown to be effective in vocal fold regeneration. However, many of the scaffold materials under investigation still await clinical translation, and those that have been investigated in human patients (such as the atelocollagen sheet) require additional research in appropriately powered placebo controlled studies.